2015
DOI: 10.1371/journal.pntd.0004239
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices (KAP) on Rift Valley Fever among Pastoralist Communities of Ijara District, North Eastern Kenya

Abstract: Outbreaks of Rift Valley fever (RVF), a mosquito-borne viral zoonosis, have previously been associated with unusually heavy rainfall and extensive flooding. The disease is a serious public health problem in Africa and the Middle East, and is a potential global health threat. In Kenya, outbreaks of the disease have disproportionately affected impoverished pastoralist communities. This study sought to assess the knowledge, attitudes and practices (KAP) regarding RVF among the pastoralists of North Eastern Kenya,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
52
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(81 citation statements)
references
References 26 publications
21
52
8
Order By: Relevance
“…This finding concurs with another study on RVF knowledge, attitudes and practices in Ijara-North Eastern Kenya, where high knowledge of preventive measures was associated with high knowledge of RVF [26]. The study further showed that high knowledge of the disease was not associated with age, sex, education, marital status, household size [26]. Another study in Kilombero and Kongwa regions in Tanzania found that besides being male or coming from Kongwa, other socio-demographic characteristics had no effect on knowledge on RVF transmission, symptoms and prevention [34].…”
Section: Discussionsupporting
confidence: 92%
“…This finding concurs with another study on RVF knowledge, attitudes and practices in Ijara-North Eastern Kenya, where high knowledge of preventive measures was associated with high knowledge of RVF [26]. The study further showed that high knowledge of the disease was not associated with age, sex, education, marital status, household size [26]. Another study in Kilombero and Kongwa regions in Tanzania found that besides being male or coming from Kongwa, other socio-demographic characteristics had no effect on knowledge on RVF transmission, symptoms and prevention [34].…”
Section: Discussionsupporting
confidence: 92%
“…Brucellosis was the least known diseases, only 2.2% know it. Addo et al from Ghana reported that TB was known by 88% of the respondents and brucellosis by 76% which is far from the findings of this study [20]. This might be due to the educational status and life experience of the respondents in Ghana.…”
Section: Discussioncontrasting
confidence: 84%
“…This is due to the lack of awareness about the health risks of milk borne diseases. A similar result was recorded in the coastal savannah zone, one of the six agro-ecological zones in Ghana by Addo et al 83.9% of the respondent did not took formal training [20].…”
Section: Discussionsupporting
confidence: 79%
“…We assessed KAP of respondents regarding SFTS based on their responses to the questionnaire provided. Table 2 shows the median (IQR) of KAP and total KAP score was 3 (1-5), 8 (6·5-9), 3 (2-3) and 13 (11)(12)(13)(14)(15)(16)(17) in the pre-invention phase and 5 (3-7), 10 (7-10), 3 (3-3) and 17 (14)(15)(16)(17)(18)(19) in the post-invention phase, respectively. The results indicated that there was a significant increase in the four type scores (Ps < 0·001).…”
Section: Impact Of the Intervention Programme On Knowledgementioning
confidence: 99%